(ایکس + 1) (ایکس + 2) (ایکس + 3) (ایکس + 4) -4؟

(ایکس + 1) (ایکس + 2) (ایکس + 3) (ایکس + 4) -4؟
Anonim

جواب:

# x ^ 4 + 10x ^ 3 + 35x ^ 2 + 50x + 20 #

وضاحت:

تقسیم ملکیت کا استعمال کریں:

# (x + 1) (x + 2) (x + 3) (x + 4) -4 #

# x ^ 4 + 6x ^ 3 + 11x ^ 2 + 6x + 4x ^ 3 + 24x ^ 2 + 44x +24- 4 #

شرائط کی طرح یکجا:

# x ^ 4 + 6x ^ 3 + 11x ^ 2 + 6x + 4x ^ 3 + 24x ^ 2 + 44x +24- 4 #

# x ^ 4 + 10x ^ 3 + 35x ^ 2 + 50x + 20 #

آپ کا جواب ہے

جواب:

# x ^ 4 + 10x ^ 3 + 35x ^ 2 + 50x + 20 #.

وضاحت:

چلو، #p (x) = (x + 1) (x + 2) (x + 3) (x + 4) -4 #, # = {(x + 1) (x + 4)} {(x + 2) (x + 3)} - 4 #, # = {x ^ 2 + 4x + x + 4} {x ^ 2 + 3x + 2x + 6} -4 #, # = (x ^ 2 + 5x + 4) (ایکس ^ 2 + 5x + 6) -4 #, # = (y + 4) (y + 6) -4 ……….. y = x ^ 2 + 5x #, # = (y ^ 2 + 6y + 4y + 24) -4 #, # = y ^ 2 + 10y + 20 #

# = (x ^ 2 + 5x) ^ 2 + 10 (ایکس ^ 2 + 5x) +20 … کیونکہ، y = x ^ 2 + 5x #

# = (x ^ 4 + 10x ^ 3 + 25x ^ 2) + (10x ^ 2 + 50x) + 20 #, # آر آر پی (x) = x ^ 4 + 10x ^ 3 + 35x ^ 2 + 50x + 20 #.